Why Have Constitutional Courts Been so Important for Democracy in Central Europe (…And So Hated by Those in Power)? - Baraník, Kamil (Journal of the University of Latvia. Law, 2018)
The contribution reacts to various thoughts about the present state of constitutionalism in the V4 countries. The author argues that the constitutional court, an institutional check on majoritarian decision-making, has been an indispensable component of constitutional-building in the Central European area. However, the model of a highly esteemed constitutional court, with its justices, nominated in a bipartisan manner, has been regularly contested, especially by those who were supposed to be constrained thereby. To outlive current and future populist waves, a result of vibrant discourse between political branches of government and a self-restrained constitutional court has a strong potential to stabilize democracy in the region, marked by authoritarian governments of the second half of the 20th century. Thus, the article will reason that we, the Central Europeans, need “more”, rather than “less” constitutionalism to protect the legacy of the last democratic revolution.